Engineering Dynamics From the Lagrangian to Simulation - Gans, Roger F. (Springer New York : Imprint: Springer, 2013)
This engineering dynamics textbook is aimed at beginning graduate students in mechanical engineering and other related engineering disciplines who need training in dynamics as applied to engineering mechanisms. It introduces the formal mathematical development of Lagrangian mechanics (and its corollaries), while solving numerous engineering applications. The author's goal is to instill an understanding of the basic physics required for engineering dynamics, while providing a recipe (algorithm) for the simulation of engineering mechanisms such as robots. The book is reasonably self-contained so that the practicing engineer interested in this area can also make use of it. This book is made accessible to the widest possible audience by numerous, solved examples and diagrams that apply the principles to real engineering applications. • Provides an applied textbook for intermediate/advanced engineering dynamics courses; • Discusses Lagrangian mechanics in the context of numerous engineering applications; • Includes numerous, solved examples, illustrative diagrams and applied exercises in every chapter.